Development of Augmented Reality Media to Enhance Students' Critical Thinking Skills in High Schools - Yonathan, Alberto Yonathan Tangke; Pramanagara, Rio Octovinary; Suhendra, Christian Dwi (Kasuari: Physics Education Journal (KPEJ), 2025)
Based on observations carried out at public high schools and private high schools in Manokwari, it was found that the physics learning used had not adapted to current technological developments, so it was less relevant when used today. The purpose of this research is to develop Augmented Reality (AR) media that is valid, practical, and effective for improving students' critical thinking learning skills on the material of rotational dynamics and equilibrium of rigid bodies in high schools in Manokwari Regency. The development method used is the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) method. The research trial was carried out on students of class XI Science at SMA YPK Oikoumene and the reel research was on students of class XI Science 1 at SMA N 2 Manokwari. This research produces AR media on the topic of rotational dynamics and equilibrium of rigid bodies which can be accessed using a computer/laptop or smartphone connected to the internet, whereas the teaching media uses AR, which can be accessed anywhere and at any time, if the Physics Augmented Reality (Phy-AR) application has been installed on an Android Smartphone so that it can improve students' critical thinking learning outcomes. This research concludes that AR media has been developed to improve the critical thinking skills of high school students and is valid, practical, and effective for use in physics learning.